2021
DOI: 10.1186/s12886-021-01957-9
|View full text |Cite
|
Sign up to set email alerts
|

USH2A gene variants cause Keratoconus and Usher syndrome phenotypes in Pakistani families

Abstract: Background Retinitis pigmentosa (RP) is the most common inherited retinal dystrophy, affecting approximately 1 in 4000 individuals worldwide. The most common form of syndromic RP is Usher syndrome (USH) accounting for approximately 20–30 % of RP cases. Mutations in the USH2A gene cause a significant proportion of recessive non-syndromic RP and USH type II (USH2). This study aimed to determine the causative role of the USH2A gene in autosomal recessive inherited ocular diseases and to establish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…In summary, eight alleles were eligible to be classified as benign/likely benign consistently by the ACMG standards, ClinVar classification system, and by majority of the online in-silico predictors. These eight benign/likely benign missense alleles are further detailed in Table 3 , and include SEMA4A (p.Arg713Gln) [ 72 ], USH2A (p.Ser2445Phe) [ 73 ], RPGRIP1 (p.Ala547Ser) [ 74 ], RP1 (p.Thr373Ile) [ 75 ], ZNF513 (p.Cys339Arg) [ 7 ], ALMS1 (p.Lys1748Glu) [ 76 ], RAX2 (p.Gly125Glu) [ 77 ], and EYS (p.Thr2777Ser) [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…In summary, eight alleles were eligible to be classified as benign/likely benign consistently by the ACMG standards, ClinVar classification system, and by majority of the online in-silico predictors. These eight benign/likely benign missense alleles are further detailed in Table 3 , and include SEMA4A (p.Arg713Gln) [ 72 ], USH2A (p.Ser2445Phe) [ 73 ], RPGRIP1 (p.Ala547Ser) [ 74 ], RP1 (p.Thr373Ile) [ 75 ], ZNF513 (p.Cys339Arg) [ 7 ], ALMS1 (p.Lys1748Glu) [ 76 ], RAX2 (p.Gly125Glu) [ 77 ], and EYS (p.Thr2777Ser) [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, causative variants in TULP1 , PDE6C , RHO , MERTK and MYO7A genes were identified in all the 4 Pakistani families displayed either non-syndromic RP or USH phenotypes using WES approach. Studies have previously reported variants in CRB1 , PDE6A , PDE6B , RP1 , TULP1, CLRN1, MERTK and CNGA1 causing non-syndromic RP and variants in MYO7A , USH2A , CDH23 , USH1H , PCDH15 genes causing USH in families of Pakistani origin [ 8 , 21 28 ]. Importantly, delineating genetic basis of RP and USH in this study and in previous studies provides essential information for molecular diagnosis as well as for genetic counselling of extended families in order to reduce burden of these diseases in Pakistani population.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally considered that about 70-80% of all RP cases are non-syndromic, where eyes are exclusively affected [ 3 ]. However, the most common syndromic form of RP is Usher syndrome (USH), characterized by sensorineural hearing loss, RP, and, in some cases, vestibular dysfunction [ 4 ]. USH is the most frequent cause of deaf-blindness and affects more than 50% of both deaf and blind individuals in different populations [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…USH2A variants display a wide phenotypic spectrum, therefore, most prevalent USH2A variants phenotype-genotype correlation may contribute to genetic counselling. It also improves the prognosis of affected individuals, and provides guideline for patient-speci c treatment [12]. USH2A (c.8559-2 A > G) variant site located in the structural domain of protein FN3 and causes an exon 43 jump, affecting protein function.…”
Section: Discussionmentioning
confidence: 99%